The Effects of TLR Activation on T-Cell Development and Differentiation - Bo Jin; Tao Sun; Xiao-Hong Yu; Ying-Xiang Yang; Anthony E. T. Yeo (Clinical and Developmental Immunology)
Invading pathogens have unique molecular signatures that are recognized by Toll-like receptors (TLRs) resulting in either activation of antigen-presenting cells (APCs) and/or costimulation of T cells inducing both innate and adaptive immunity. TLRs are also involved in T-cell development and can reprogram Treg cells to become helper cells. T cells consist of various subsets, that is, Th1, Th2, Th17, T follicular helper (Tfh), cytotoxic T lymphocytes (CTLs), regulatory T cells (Treg) and these originate from thymic progenitor thymocytes. T-cell receptor (TCR) activation in distinct T-cell subsets with different TLRs results in differing outcomes, for example, activation of TLR4 expressed in T cells promotes suppressive function of regulatory T cells (Treg), while activation of TLR6 expressed in T cells abrogates Treg function. The current state of knowledge of regarding TLR-mediated T-cell development and differentiation is reviewed.